Representação social do hospital para as crianças doentes: o papel da mediação pedagógica - Barone, Beatriz Vieira (Universidade Federal de São Carlos, 2025)
The hospitalization of a child represents a complex and challenging moment, influencing not only their physical health but also their social, emotional, and educational development. The distance from family, friends, school, and daily activities can trigger feelings of fear, anxiety, sadness, loneliness, regression, and even trauma. The present research aimed to analyze the social representation of the hospital for sick children through pedagogical mediation using the Drawing-Story with Theme technique. This was a pedagogical intervention study, with a qualitative approach and descriptive design. The study was carried out in the playroom of a pediatric ward located in a philanthropic hospital in a medium-sized city in the interior of the state of São Paulo. Ten children between six and ten years of age participated, as well as their respective caregivers. Data collection occurred through five stages: [1] application of a semi-structured interview script with the caregiver; [2] request for the child to create a Drawing-Story with the theme "hospital"; [3] semi-structured interview with the child; [4] development and implementation of school-based pedagogical activities, with analysis and feedback from the children regarding the pedagogical mediation; [5] request for a new Drawing-Story with the theme "hospital after the experience with the teacher." The initial drawings revealed two perceptions of the hospital. On the one hand, positive aspects related to the care provided by the nursing staff; on the other hand, negative aspects related to the wait for medical care, the venipuncture procedure, and prolonged bed rest. The pedagogical mediation was structured through three school-based educational activities: storytelling, curricular activity, and game. For the analysis, results from an observation protocol applied by a research assistant were used, highlighting the actions of the teacher/researcher and the child's responses within the axes of instruction, development, and feedback. The pedagogical mediation highlighted the positive impacts of the teacher-student relationship, significantly contributing to the children's well-being and enabling experiences of joy, learning, and play, even amid the adversities of the hospital context. The drawings produced after this intervention introduced new characters into the hospital setting, such as the playroom, the teacher, the research assistant, and the game, emphasizing the importance of play and study within this environment. In view of this, the importance of the study is emphasized for understanding children's perspectives on the hospital environment and for ensuring their right to educational continuity, promoting not only cognitive development but also the recovery of their identity and well-being.
Social representation of the hospital for sick children: the role of pedagogical mediation
Keywords: Educação Especial; Representação social; Criança doente; Hospital; Mediação pedagógica; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::PSICOLOGIA